Ensaios de José Honório Rodrigues: em busca de uma historiografia brasileira - Uhiara, Érika [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
José Honório Rodrigues is considered, among Brazilian historians, precursor of historiographical approach in the History of Brazil. By tracking a broader movement of renewal of interest in Brazilian historiography history, this study sought to analyze the essays published by Rodrigues, between the 50s and 80s of the twentieth century, in order to progress in the knowledge of his reflections about the nature and what he considered, at that time, as new perspectives of the work of the historian. Part of this material belongs to the 3rd stage of the audacious incomplete historiographical project of Rodrigues on research, theory, history of Brazilian history, a project he developed up to the time of his death in 1987. It was assumed that the production of Rodrigues' essays constituted up the appropriate basis to the disclosure and the establishment of faster and more direct dialogues with his peers, since the Rodrigues was not in a regular chair in any of the Brazilian Universities. Alongside the greater scope works, the essays produced by the author allowed us to understand the development of his historiographical project over four decades, as well as his proposal to transform the social and historical reality of Brazil through a historical culture

José Honório Rodrigues é considerado, entre os historiadores brasileiros, precursor de uma abordagem historiográfica da História no Brasil. Ao acompanhar um movimento mais amplo de renovação do interesse pela história da historiografia brasileira, esta pesquisa procurou analisar os ensaios publicados por Rodrigues, entre as décadas de 50 e 80 do século XX, para avançar no conhecimento de suas reflexões a respeito da natureza e do que considerou, à época, como novas perspectivas do trabalho do historiador. Parte deste material pertence a 3ª etapa incompleta do audacioso projeto historiográfico de Rodrigues sobre pesquisa, teoria e história da história do Brasil, projeto que desenvolveu até sua morte, em 1987. Partiu-se do pressuposto de que a produção ensaística de Rodrigues constituía-se no suporte adequado à divulgação e ao estabelecimento de diálogos mais rápidos e diretos com seus pares, uma vez que o estudioso não ocupava uma cátedra regular em nenhuma das universidades brasileiras. Ao lado das obras de maior fôlego, os ensaios produzidos pelo autor permitiram compreender o desenvolvimento do seu projeto historiográfico ao longo de quatro décadas, assim como, sua proposta de transformação da realidade social e histórica do Brasil através de uma cultura histórica
Keywords: Rodrigues, Jose Honorio - 1913-1987; História; Ensaios brasileiros; Historiografia; Historiadores - História - Brasil; Brasil - Historiografia - Séc. XX; History